Risk Management of Distance Education Library open access services at the Universitas Terbuka in the covid 19 era - Mohamad Pandu Ristiyono (SAJMR : Southeast Asian Journal of Management and Research, 2024)
This paper discusses risk management in open access services for distance education libraries at the Open University in the COVID-19 era. In the context of the COVID-19 pandemic, distance education libraries are faced with new challenges that affect the smooth running of services to distance students. Therefore, risk management is an important aspect that needs to be considered in order to ensure the smooth running of library services. The research method used in this paper involves literature study and risk analysis. The literature study was conducted to gain an in-depth understanding of the concept of risk management, the challenges faced, and the strategies that can be implemented. Furthermore, risk analysis was conducted to identify potential risks that may be faced by distance education libraries in the COVID-19 era. The results showed that the risks identified include aspects of data security, where increased access to virtual reading rooms (RBV), but there is also an emerging phenomenon, namely tutorials on how to download virtual reading rooms (RBV) on YOUTUBE. several strategies can be implemented, including the use of appropriate technology, training and education for users, as well as policies that support the sustainability and development of libraries. This paper provides insights and practical guidance for distance education library managers at the Open University and related parties in managing risks and ensuring the smooth running of library services during the COVID-19 pandemic. By combining the right risk management approach with technology and innovation, distance education libraries can continue to provide quality services to students, ensure access to necessary information resources, and support effective learning processes amid the COVID-19 pandemic